Metallic stent with high axial force as a risk factor for cholecystitis in distal malignant biliary obstruction. Issue 7 (15th July 2014) - Nakai, Yousuke; Isayama, Hiroyuki; Kawakubo, Kazumichi; Kogure, Hirofumi; Hamada, Tsuyoshi; Togawa, Osamu; Ito, Yukiko; Matsubara, Saburo; Arizumi, Toshihiko; Yagioka, Hiroshi; Takahara, Naminatsu; Uchino, Rie; et al.
Abstract Background and Aim Tumor involvement to the orifice of cystic duct (OCD) is a risk factor for cholecystitis after self‐expandable metallic stent (SEMS) placement, but its prevention is still difficult. We conducted this multicenter analysis to clarify a type of SEMS or a method to place SEMS which would decrease the incidence of cholecystitis after SEMS placement. Methods The incidence of cholecystitis was studied in consecutive patients receiving SEMS for distal malignant biliary obstruction in five tertiary care centers. Multiple logistic regression analysis was performed to evaluate risk factors for cholecystitis. Results A total of 376 patients who received SEMS placement for distal malignant biliary obstruction were analyzed. Tumor involvement to OCD was diagnosed in 25.3%. Overall incidence of cholecystitis was 6.9%. Cholecystitis was observed in 8.0% of 300 patients with covered SEMS, 16.8% of 95 patients with tumor involvement to OCD, 10.8% of 234 patients with SEMS of high axial force (AF), and 12.0% of 158 patients with SEMS length ≤ 60 mm. In the multivariate analysis, tumor involvement to OCD (odds ratio [OR] 5.40, P < 0.001), SEMSs with high AF (OR 5.33, P = 0.002), and SEMS length ≤ 60 mm (OR 3.19, P = 0.010) are risk factors. Among patients with tumor involvement to OCD, the incidence of cholecystitis in SEMS with high and low AF was 25.0% and 5.0%, respectively. Conclusion This study with an expanded cohort reconfirmed tumor involvement to OCD as a risk factor for cholecystitis after SEMS placement. SEMS with low AF might decrease cholecystitis.